2006
DOI: 10.1007/bf03194607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy metal pollution on genetic variation and cytological disturbances in thePinus sylvestris L. population

Abstract: This isoenzymatic and cytogenetic study has shown significant differences in genetic composition between two groups of Pinus sylvestris trees: tolerant and sensitive to heavy metal pollution. Total and mean numbers of alleles and genotypes per locus were higher in the pollution-sensitive group of trees, but heterozygosity (Ho) was lower in this group. Fixation index (F) indicates that trees tolerant for pollution were in the Hardy-Weinberg equilibrium, while the sensitive group had a significant excess of homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…In agreement with our findings, several studies on Scots pine reported genetic associations between growth rate and air pollution tolerance (Oleksyn et al 1992, 1994, Prus-Glowacki et al 2006. Furthermore, if heritability for pollution tolerance in pines is greater than for growth rate (Thor & Gall 1978), then it is logical to assume that the heritability for annual increments under the pollution stress is relatively greater, as observed in our study.…”
Section: Var(c)supporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our findings, several studies on Scots pine reported genetic associations between growth rate and air pollution tolerance (Oleksyn et al 1992, 1994, Prus-Glowacki et al 2006. Furthermore, if heritability for pollution tolerance in pines is greater than for growth rate (Thor & Gall 1978), then it is logical to assume that the heritability for annual increments under the pollution stress is relatively greater, as observed in our study.…”
Section: Var(c)supporting
confidence: 92%
“…Though the genetic tolerance experiments are less abundant, there is a strong indication of a genetic component in the pollution stress tolerance (Bergmann & Scholz 1987b, Korshikov et al 2002, Prus-Glowacki et al 2006. Several independent studies reported a positive relationship between the genetic polymorphism of trees and their tolerance to air pollution (Geburek et al 1987, Oleksyn et al 1994, Prus-Glowacki et al 2006). There was a significant Scots pine provenance variation in tolerance to air pollution in the vicinity of a nitrogen fertilizer plant in Poland (Oleksyn et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Their genotoxic effects depend on the oxidation state of the metal, their concentration and the duration of exposition, and these are more pronounced at high concentrations and after a long exposition time (Cosio et al, 2005). Cytological analyses demonstrate numerous aberrations of chromosomes in meristematic root tissue of seedlings developed from seeds collected from trees in the polluted area, including chromosome bridges and stickiness, laggards, retarded and forward chromosomes, and their fragments (Prus-Glowacki et al, 2006).…”
Section: Natural and Anthropogenic Factors Affecting The Bioavail-abimentioning
confidence: 99%
“…The heavy metals Pb and Cd induce chromosomal aberrations and disturbed mitotic divisions in the Pinus sylvestris population (Prus-Glowacki et al, 2006). However, plants show considerable constitutional tolerance to Pb and, in some cases, reach levels of induced tolerance (Sharma and Dubey, 2005).…”
Section: Mechanisms Of Resistance or Tolerance To Metals In Plantsmentioning
confidence: 99%
“…Metals impose severe stress on plants, especially in the rooting zone, which has led to the evolution of metal-resistant ecotypes in several herbaceous species like D. cespitosa (Cox and Hutchinson 1980). Evidence of loss of genetic variation based on enzymatic analysis at the population level caused by pollution has been demonstrated in some species (Lopes et al 2004;Prus-Glowacki et al 2006;van Straalen and Timmermans 2002). But, plants possess homeostatic cellular mechanisms to regulate the concentration of metal ions inside the cell to minimize the potential damage that could result from the exposure to nonessential metal ions.…”
Section: Discussionmentioning
confidence: 99%